Lipoma of the middle finger: A case report and review of literature. Issue 42 (October 2017) - Hu, Zhongqing; Yue, Zhenshuang; Tang, Yanghua; Zhu, Yi
Abstract: Rationale: Lipomas originated from fingers are rare and the dissection is necessary when the lipomas limit the finger movement or cause pain. Patient concerns: A 57-year-old male was admitted to our department due to a painless swelling on the volar side of the middle finger of the right hand. The flexion movement of the distal interphalangeal joint was limited. Diagnoses: : Imaging studies and open biopsy confirmed that it was a finger lipoma. Interventions: : An excisional biopsy was performed. Outcomes: : The patient recovered completely after two weeks. Lessons: : Based on this case and literature we reviewed, ultrasound and MRI should be used to diagnose the finger lipoma and excision was the main treatment option.